2002
DOI: 10.1139/b02-003
|View full text |Cite
|
Sign up to set email alerts
|

Species richness, abundance, and composition of hypogeous and epigeous ectomycorrhizal fungal sporocarps in young, rotation-age, and old-growth stands of Douglas-fir (Pseudotsuga menziesii) in the Cascade Range of Oregon, U.S.A.

Abstract: Knowledge of the community structure of ectomycorrhizal fungi among successional forest age-classes is critical for conserving fungal species diversity. Hypogeous and epigeous sporocarps were collected from three replicate stands in each of three forest age-classes (young, rotation-age, and old-growth) of Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) dominated stands with mesic plant association groups. Over four fall and three spring seasons, 48 hypogeous and 215 epigeous species or species groups were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
118
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(140 citation statements)
references
References 47 publications
(111 reference statements)
19
118
2
1
Order By: Relevance
“…Several studies have demonstrated that the composition of fungal communities changes during the forest succession (Hintikka 1988;Last et al 1987;Dighton et al 1986). Smith et al (2002) and Kranabetter et al (2005) showed that, in older mixed conifer stands, the fruit-body biomass and the frequency of several 'late-stage' fungi were greater than in younger stands. Recently, however, Twieg et al (2007) demonstrated that simple categories such as 'early stage', 'multi stage' and 'late stage' were insufficient to describe fungal species' successional patterns in Douglas fir (Pseudotsuga menziesii) stands.…”
Section: Impact Of Atmospheric Input Of Nitrogenmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have demonstrated that the composition of fungal communities changes during the forest succession (Hintikka 1988;Last et al 1987;Dighton et al 1986). Smith et al (2002) and Kranabetter et al (2005) showed that, in older mixed conifer stands, the fruit-body biomass and the frequency of several 'late-stage' fungi were greater than in younger stands. Recently, however, Twieg et al (2007) demonstrated that simple categories such as 'early stage', 'multi stage' and 'late stage' were insufficient to describe fungal species' successional patterns in Douglas fir (Pseudotsuga menziesii) stands.…”
Section: Impact Of Atmospheric Input Of Nitrogenmentioning
confidence: 98%
“…Of these, 70% occur in forests and about half of them are mycorrhizal. Forest fungi play important ecological roles in forest ecosystems, acting as mycorrhizal symbionts, decomposers and pathogens (Smith and Read 1997;Dighton et al 2005). In addition, picking their fruit bodies is a popular pastime and a recreational activity for many people in a substantial number of countries (Boa 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This may suggest that our sampling effort was insufficient to detect many rare taxa. However, the dominance of rare taxa occurs in species-rich ECM assemblages of old sampled stands (old-growth stage; O'Dell et al 1999;Richard et al 2005;Smith et al 2002). The ECM communities may thus reflect more the age of the tree individuals (age of root systems) than the age of stems since the last clear-cut.…”
Section: Structure and Richness Of Ecm Communities In Q Ilex Coppicesmentioning
confidence: 99%
“…Impacts on truffle production, however, were brief. The long-term impacts of forest management on truffle production remain unclear, with inconsistent results from across the region , Smith et al 2002. Induced heterogeneity increased sporocarp diversity to a richness that rivals that in old growth .…”
Section: Discussionmentioning
confidence: 99%